Advanced Glycation Risk in Diabetic Nutritional Supplements: GC-MS-Based Quantification of key Dicarbonyl Compounds - Ranjani, C.A. Sri; Deepti, C Asha (Journal of Neonatal Surgery, 2025)
Methylglyoxal (MGO) and glyoxal (GO) are highly reactive α-dicarbonyl compounds implicated in numerous pathological conditions and frequently formed during food processing and storage. Due to their potential health risks, especially among diabetic populations, precise quantification in widely consumed protein supplements is critical. This study presents a validated, sensitive gas chromatography/mass spectrometry (GC/MS) method utilizing 3,3',5,5'-tetramethylbenzidine (TMB) for derivatization of MGO and GO in various protein supplements, including diabetes-specific formulations. The developed method exhibited outstanding linearity (R² ≥ 0.999), low detection limits (GO: 0.005 µg/mL, MGO: 0.01 µg/mL), and high recovery rates (85–95%). Commercial diabetes care protein powders demonstrated significantly elevated MGO (2.93–4.14 µg/mL) and GO (22.36–32.40 µg/mL) levels, while raw protein powders contained the lowest concentrations. The data emphasize the impact of processing on dicarbonyl formation and underscore the necessity of regular monitoring to ensure consumer safety and product integrity.